Identification of QTLs controlling resistance/tolerance to Striga hermonthica in an extra-early maturing yellow maize population - Badu-Apraku, Baffour; Adewale, Samuel A.; Agre, A.P.; Gedil, Melaku A; Asiedu, R. (MDPI, 2020)
Striga hermonthica parasitism is a major constraint to maize production in sub-Saharan Africa with yield losses reaching 100% under severe infestation. The application of marker-assisted selection is highly promising for accelerating breeding for Striga resistance/tolerance in maize but requires the identification of quantitative trait loci (QTLs) linked to Striga resistance/tolerance traits. In the present study, 194 F2:3 families of TZEEI 79 × TZdEEI 11 were screened at two Striga-endemic locations in Nigeria, to identify QTLs associated with S. hermonthica resistance/tolerance and underlying putative candidate genes. A genetic map was constructed using 1139 filtered DArTseq markers distributed across the 10 maize chromosomes, covering 2016 cM, with mean genetic distance of 1.70 cM. Twelve minor and major QTLs were identified for four Striga resistance/tolerance adaptive traits, explaining 19.4%, 34.9%, 14.2% and 3.2% of observed phenotypic variation for grain yield, ears per plant, Striga damage and emerged Striga plants, respectively. The QTLs were found to be linked to candidate genes which may be associated with plant defense mechanisms in S. hermonthica infested environments. The results of this study provide insights into the genetic architecture of S. hermonthica resistance/tolerance indicator traits which could be employed for marker-assisted selection to accelerate efficient transfer host plant resistance genes to susceptible genotypes.